THE ENTREPRENEURIAL INTENTION OF UNIVERSITY STUDENTS IN BRAZIL - Dias, Á.; Carvalho, João; Madeira, MJ; Carvalho, Fábio (62nd International Scientific Conference on Economic and Social Development, 2020)
The purpose of this study is to increase the understanding of how the entrepreneurial potential is developed among students. The research aimed to study the factors that impact the entrepreneurial intention of young university students. Changes in individuals' entrepreneurial intentions and the antecedents of intentions are investigated, as well as the impact of entrepreneurship education on changes. The Theory of Planned Behavior was applied to 204 students from public and private colleges in the state of Maranhão, Brazil, during 2019. The data were collected using a five-point Likert scale questionnaire and analyzed by factor analysis and regression. The results indicated that personal attitudes are factors capable of predicting entrepreneurial intention, corroborating previous studies. The analysis of the control variable of the perceived behavior reveals that the students, although they affirm that they are ready to start new businesses, does not reveal enough strength to predict the entrepreneurial intention. The pressure from social groups represented by the subjective norms factor did not reveal significant correlations with the entrepreneurial intention. Educational support has a strong impact on entrepreneurial intent, although active methodologies contribute little to this mediation.